SCAFFOLDING IN TEACHING WRITING NEWS ITEM TEXT, ITS BENEFITS AND CHALLENGES - Mayang Sari Nirmala Dewi; Rahma Sakina; Eva Meidi Kulsum; Aip Syaepul Uyun; Riyadh Ahsanul Arifin (English Review: Journal of English Education, 2023)
The research aimed at investigating types of scaffolding, the ways a teacher provides scaffolding, and benefits and challenges of scaffolding in teaching writing News Item text in tenth graders in a senior high school in Bandung. This research employed a qualitative research design, embracing characteristic of a case study. The data were obtained from non-participant classroom observation for six meetings, and one interview. The data collected from classroom observation and interview were transcribed and then analyzed by using framework of types of scaffolding (e.g Roehler and Cantlon (1997), Hammond (2001), Gibbons, (2002), and Walqui (2006)). The findings revealed that seven types of scaffolding were provided by the teacher   during teaching writing News Item text. The most intensive scaffolding was given in the Modeling stage, while scaffolding was removed in the Independent Writing stage. Regarding the benefits and challenges of providing scaffolding, this research found out the benefits of scaffolding such as to connect students’ prior knowledge with a new concept, to engage students, to minimize the level confusion of students, and to build students‟ self-confidence. Meanwhile, the challenges of providing scaffolding are the number of students in the classroom, time constraints, and demands on teacher.